A study on cryptosporidium spp. isolated from children with diarrhoea admitted to Selayang Hospital and Sungai Buloh Hospital in Selangor, Malaysia / Nurul Fariza Rossle - Rossle, Nurul Fariza (2016)
This study was conducted to verify the prevalence of cryptosporidiosis among children in Selangor. Consenting children aged 12 years and below, admitted with diarrhoea to Hospital Selayang and Hospital Sungai Buloh or contracting diarrhoea in hospitalization, were included as subjects. Each stool sample was distributed into six aliquots and tested for cryptosporidiosis using direct wet mount. Sheather’s sugar flotation, formalin-ether sedimentation, modified Ziehl-Neelsen staining, direct monoclonal fluorescent antibody, and polymerase chain reaction (PCR). Out of 160 stool samples, 6 (3.75%) were positive for Cryptosporidium spp. All children positive for cryptosporidiosis were aged <4 years. Direct wet mount, formalin-ether sedimentation concentration, modified Ziehl-Neelsen staining, and direct monoclonal fluorescent antibody testing showed the same number of positive samples (3.75%). Sheather's sugar flotation detected one less positive sample (3.13%). No noticeable DNA bands were observed on the electrophoresed gel from stool sample amplification, although there were faint bands for positive control using purified Cryptosporidium oocysts. The youngest child infected was 6 months old while the oldest was 3 years 4 months old. Same number of males and females were infected with four Malays and one Chinese and Indian each. There is no significant association between Cryptosporidium infection with gender and race. Age posed the most significant difference with all infected children being less than four years old. Further molecular epidemiological study on a larger scale incorporating humans, animals and environmental samples from the whole of Malaysia is recommended to clarify the dynamic of Cryptosporidium transmission in the country.